HUMAN SPACE FLIGHTS: FACTS AND DREAMS - Mariano Bizzarri; Enrico Saggese (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2011)
Manned space flight has been the great human and technological adventure of the past half-century. By putting people into places and situations unprecedented in history, it has stirred the imagination while expanding and redefining the human experience. However, space exploration obliges men to confront a hostile environment of cosmic radiation, microgravity, isolation and changes in the magnetic field. Any space traveler is therefore submitted to relevant health threats. In the twenty-first century, human space flight will continue, but it will change in the ways that science and technology have changed on Earth: it will become more networked, more global, and more oriented toward primary objectives. A new international human space flight policy can help achieve these objectives by clarifying the rationales, the ethics of acceptable risk, the role of remote presence, and the need for balance between funding and ambition to justify the risk of human lives.